Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran SBdP Melalui Penggunaan Media Animasi Di kelas V SD GKST TARIPA - Bamolele, Agles; Lagandesa, Yun Ratna; Ryan Andika Pratama; Kadek Hariana (JURNAL DIKDAS, 2023)
Learning media is an integral component of the learning system. This means that learning media cannot be separated from the learning process. Without learning media, the teaching and learning process cannot occur and there are no good learning outcomes. Animation is basically a series of images that form a movement that has advantages over other media such as static images or text. Animation to attract students' attention and strengthen motivation is usually in the form of writing or moving images. This study aims to improve student learning outcomes in the subject of Arts and Culture in class V of GKST Taripa Elementary School through animation media. The type of research used is PTK using two cycles. Which aims to measure the extent to which student learning outcomes in the subject of Arts and Culture Using Animation Media in Class V of GKST TARIPA Elementary School. Based on the results of the study, applying animation media can improve the learning outcomes of Arts and Culture of class V students of GKST TARIPA Elementary School. The results of the pre-action showed an average value of student learning outcomes of 18.38% and classical learning completeness of 38.71%. The results of the first cycle of action showed an average value of student learning outcomes of 65.16% and classical learning completeness reached 74.19%. The results of cycle II actions showed an average value of student learning outcomes of 82.90% and classical learning completion of 93.55%.